Standard Clauses in Vehicle Purchase Credit Agreements in Indonesia: An Examination of Consumer Protection and Legal Enforcement - Jovita Irawati; Kevin Gorga Kennedy Hutagalung (Journal of Judicial Review, 2023)
Vehicle purchase credit agreements in Indonesia frequently incorporate standard clauses that are often perceived as offering inadequate legal protection to consumers. Despite clear prohibitions regarding the use of standard clauses in credit agreements, vehicle financing businesses often persist in implementing these clauses in their contracts with consumers. Consequently, consumers find themselves in an unfavorable position, lacking the necessary legal safeguards to protect their rights. Consumers are entitled to legal protection, legal certainty, and justice when engaging with consumer financing institutions. This study employs a qualitative analysis approach, utilizing the normative legal research method to interpret legal materials, including court decisions. The research findings reveal that consumer protection regulations pertaining to standard clauses in vehicle purchase credit agreements have been distinctly and sufficiently defined. However, the enforcement of laws and stringent sanctions against violations has not been fully effective.